2020
DOI: 10.1111/nana.12607
|View full text |Cite
|
Sign up to set email alerts
|

Producing the nation through philanthropy: Legitimising coethnic and prorefugee civic action in Hungary

Abstract: This paper explores interconnections between nationhood and philanthropy, namely, how philanthropy works as a domain of meaningful social practice framed by national ideologies and how interpretations born in the institutional contexts of philanthropy may play a central role in making sense of the nation. We observe how various divisions inherent in philanthropic practices—between helpers and the helped and between those who take part in helping as opposed to those who do not—become reflected in concepts of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Readers may challenge the generalisability of the results of such a specific form of philanthropy, based on an explicitly particularistic ideology, and its relevance to phenomena usually conceptualised as based on universalist concepts of poverty alleviation or humanitarianism. Against these challenges this paper claims that studies of philanthropy, charity, or humanitarianism have recently explored potential particularistic roots of various allegedly universalist initiatives, and questioned clear-cut divides and boundaries between them (for example Malkki, 2015;Drazkiewicz, 2020;Zakaria ´s & Feischmidt, 2020). These scholarly works have revealed that, instead of defining distinct types of philanthropic support, various conceptual frameworks and ideologies-particularistic as well as universalist-are rather layered upon each other and may simultaneously, in concert provide the moral foundations of giving and helping.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Readers may challenge the generalisability of the results of such a specific form of philanthropy, based on an explicitly particularistic ideology, and its relevance to phenomena usually conceptualised as based on universalist concepts of poverty alleviation or humanitarianism. Against these challenges this paper claims that studies of philanthropy, charity, or humanitarianism have recently explored potential particularistic roots of various allegedly universalist initiatives, and questioned clear-cut divides and boundaries between them (for example Malkki, 2015;Drazkiewicz, 2020;Zakaria ´s & Feischmidt, 2020). These scholarly works have revealed that, instead of defining distinct types of philanthropic support, various conceptual frameworks and ideologies-particularistic as well as universalist-are rather layered upon each other and may simultaneously, in concert provide the moral foundations of giving and helping.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…As for philanthropy, various ethnographic, anthropological and sociological studies focus on the possible enhanced role of personal relations between donors and recipients of help (for an overview of the topic: Fechter, 2019). Among these several authors have taken notice of the working of kinship and familial idioms and metaphors in the construction of personal donor-recipient relationships: in case of international development and humanitarian child-sponsorship (Bornstein, 2001(Bornstein, , 2012Dra ˛_ zkiewicz, 2020;Fechter, 2019;Noh, 2019;Rabbitts, 2012;Zarzycka, 2016;Zakaria ´s & Feischmidt, 2020), in personal mentoring schemes of disadvantaged students built upon volunteering in educational and welfare settings (Molpeceres et al, 2012), in a historical account of donor identity formation by the Red Cross (Dromi, 2021), and more recently in personalised helping and mentoring of refugee minors residing in Western European countries (Raithelhuber, 2019;Scheibelhofer, 2019;Aflaki & Freise, 2019).…”
Section: Kinship Idioms In Philanthropy Researchmentioning
confidence: 99%
“…The article aims to contribute to understanding how intra-EU migrants, employed or volunteering in these organisations, rely and mobilise various frameworks of deservingness while relating to their refugee clients and students. Despite these wider stakes, we narrowed our empirical focus on workers of Hungarian background as a direct continuation of previous research conducted in Hungary on pro-refugee civic initiatives (Feischmidt and Zakariás, 2019; Zakariás and Feischmidt, 2020).…”
Section: Methodology and Datamentioning
confidence: 99%
“…In such a polarised political field, education has become a battlefield of a symbolic struggle for reinstating the nation since 2010 (Zakariás, 2014). In the following, I draw a quick sketch of the main compulsory education policies to provide my analysis with background.…”
Section: Education Policy-making In Hungary Since 2010mentioning
confidence: 99%